2020
DOI: 10.1074/mcp.ra120.001946
|View full text |Cite
|
Sign up to set email alerts
|

Proteome and Phosphoproteome Analysis of Brown Adipocytes Reveals That RICTOR Loss Dampens Global Insulin/AKT Signaling

Abstract: Stimulating brown adipose tissue (BAT) activity represents a promising therapy for overcoming metabolic diseases. mTORC2 is important for regulating BAT metabolism, but its downstream targets have not been fully characterized. In this study, we apply proteomics and phosphoproteomics to investigate the downstream effectors of mTORC2 in brown adipocytes. We compare wild-type controls to isogenic cells with an induced knockout of the mTORC2 subunit RICTOR (Rictor-iKO) by stimula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 39 publications
2
2
0
Order By: Relevance
“…The connection between increase in mitochondrial functions and resistance to BRAFi is supported by our experimental evidence, as both NAMPT and ETC inhibition reverses the BRAFi tolerance of RICTOR-depleted cells. Our findings are supported by previous works that show NDUFS1 modulation by posttranslational modifications, and by poorly-characterized associations between RICTOR downregulation and gain of mitochondrial functions [18,19,48].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The connection between increase in mitochondrial functions and resistance to BRAFi is supported by our experimental evidence, as both NAMPT and ETC inhibition reverses the BRAFi tolerance of RICTOR-depleted cells. Our findings are supported by previous works that show NDUFS1 modulation by posttranslational modifications, and by poorly-characterized associations between RICTOR downregulation and gain of mitochondrial functions [18,19,48].…”
Section: Discussionsupporting
confidence: 91%
“…Notably, the metabolic phenotype found in RICTORknockout keratinocytes, consisting of a switch from a glycolytic-to an OXPHOS-based energetic metabolism fueled by glutamine consumption, is reminiscent of that of targeted therapy-resistant melanoma cells. Consistently, RICTOR deficiency was previously associated with the induction of genes and/or cellular processes that favor mitochondrial ATP synthesis [18][19][20][21]. Based on these notions, we have hypothesized that RICTOR/ mTORC2 deficiency in BRAF V600E melanoma cells may favor BRAF/MEKi resistance.…”
Section: Introductionsupporting
confidence: 58%
“…Most pronounced programming effect across all tissues at the level of individual upstream regulators was inhibition of RICTOR, a regulatory subunit of the mammalian target of rapamycin complex 2. Loss of RICTOR leads to the global dampening of insulin/AKT signaling ( Entwisle et al, 2020 ). Although this observation did not translate to change of global glucose tolerance in the programmed rat offspring, subtler change in insulin resistance of peripheral tissues cannot be excluded, as suggested by the 3-fold (2-fold in SHR- Zbtb16 ) reduction of Glut4 expression in white adipose tissue of SHR male offspring and, in a network perspective, the glucose metabolism disorder activated node.…”
Section: Discussionmentioning
confidence: 99%
“…Recent advances in mass spectrometry (MS)-based phosphoproteomics have enabled widespread quantification of phosphorylation dynamics in diverse biological contexts and organisms [15][16][17][18] . Global studies in skeletal muscle, adipose tissue, and liver of rodents and humans have revealed that insulin regulates thousands of phosphosites on hundreds of proteins 3,4,[19][20][21][22][23] . A major challenge now lies in identifying the connectivity and functionally annotating these signalling networks.…”
Section: Introductionmentioning
confidence: 99%